Duckweed as a Feed Ingredient in Laying Hen Diets and its Effect on Egg Production and Composition - Anderson, K.E.; Lowman, Z.; Stomp, Anne-Marie; Chang, Jay (International Journal of Poultry Science, 2010)
Duckweed, a prolific aquatic plant, can be used for products including: biofuels (ethanol) and animal feeds. Researchers at North Carolina State University have worked for a decade to develop a system to produce high-protein duckweed biomass utilizing the nutrient-rich effluent from anaerobic digestion of swine wastewater. This aspect of the project was to evaluate a feeding trial utilizing duckweed materials as a protein source in laying hen feed. The nutrient and energy composition of the Duckweed grown in these conditions was determined, then the impact of duckweed in a commercial layer diet on egg production and feed conversion was evaluated. The duckweed samples analyzed contained 29.05% CP, 25.08% C Fiber and 695 kcal/kg AMEn based on a feeding trial with marker. The analysis was used to formulate a layer diet containing 12.6% duckweed. Both the Control (C) and Duckweed (D) diets were formulated to be Iso-nitrogenous (18.1% Crude Protein) and Iso-caloric (2930 kcal/kg). Sixty Hy-Line, w-36 hens were randomly divided into 4 replicates each containing 15 hens from 76-88 wks of age, 2 replicates were placed on the C Diet and the remaining 2 were fed the D diet. Feed consumption and egg production monitored daily and each wk one days collection was analyzed for USDA Grades, haugh unit, shell strength, vitelline membrane strength and yolk color. On wks 3, 7 and 11 whole 6 egg pooled samples were collected and sent in for nutrient composition laboratory analysis. The D diet had no impact on the hen performance over that of the C diet group, 71.1 and 69.5% hen-day production, respectively. There was a significant increase in the percent Grade B eggs in the hens fed the D by 2% over the C hens. Surprisingly, there was no difference in the nutrient composition of the eggs except for Omega 3 levels which were 0.06 % higher (P